2016
DOI: 10.1186/s12958-016-0146-0
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic pregnancy risk factors for ART patients undergoing the GnRH antagonist protocol: a retrospective study

Abstract: BackgroundIn-vitro fertilization is a known risk factor for ectopic pregnancies. We sought to establish the risk factors for ectopic pregnancy in GnRH antagonist cycles examining patient and stimulation parameters with an emphasis on ovulation trigger.MethodsWe conducted a retrospective, cohort study of 343 patients undergoing 380 assisted reproductive technology (ART) cycles with the GnRH antagonist protocol and achieving a clinical pregnancy from November 2010 through December 2015.ResultsSignificant risk fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
3

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 61 publications
1
23
3
Order By: Relevance
“…An increased risk for EUP was reported in GnRH antagonist fresh autologous cycles as compared to the luteal GnRHa long protocol [36]. It has also been suggested that GnRHa triggering might be related to a higher incidence of EUP [37][38][39]. In this study, only 3 EUP occurred, and hence, no conclusion can be drawn.…”
Section: Discussioncontrasting
confidence: 53%
“…An increased risk for EUP was reported in GnRH antagonist fresh autologous cycles as compared to the luteal GnRHa long protocol [36]. It has also been suggested that GnRHa triggering might be related to a higher incidence of EUP [37][38][39]. In this study, only 3 EUP occurred, and hence, no conclusion can be drawn.…”
Section: Discussioncontrasting
confidence: 53%
“…In addition, luteal GnRH antagonist administration in women with severe early ovarian hyperstimulation syndrome (OHSS) is associated not only with not different live birth rates but also with similar duration of gestation (36.9 ± 0.9 vs. 36.9 ± 2.4 weeks) and neonatal weight (2392 ± 427 vs. 2646 ± 655 g) when compared to patients who do not receive the treatment [47]. However, in patients undergoing COH using the GnRH antagonist protocol, GnRH agonist trigger were found to be independent risk factors for ectopic pregnancy [48]. …”
Section: Resultsmentioning
confidence: 99%
“…No TET was performed in the center. Our protocols for COS, endometrial preparation, as well as laboratory procedures have been described elsewhere [14][15][16].…”
Section: Systematic Review and Meta-analysismentioning
confidence: 99%